Elite swimmers internal markers trajectories in ecological training conditions; Scandinavian Journal of Medicine and Science in Sports; Vol. 28, iss. 8 - Vacher Ph. Philippe; Martinent G. Guillaume; Mourot L. Laurent; Nicolas M. Michel (2018, 2018)
Title screen